Taper-free and kinked germanium nanowires grown on silicon via purging and the two-temperature process. - Kim, J; Moon, SR; Kim, Y; Chen, Z; Zou, J; Choi, D; Joyce, H; Gao, Q; Tan, H; Jagadish, C (2012)
We investigate the growth procedures for achieving taper-free and kinked germanium nanowires epitaxially grown on silicon substrates by chemical vapor deposition. Singly and multiply kinked germanium nanowires consisting of <111> segments were formed by employing a reactant gas purging process. Unlike non-epitaxial kinked nanowires, a two-temperature process is necessary to maintain the taper-free nature of segments in our kinked germanium nanowires on silicon. As an application, nanobridges formed between (111) side walls of V-grooved (100) silicon substrates have been demonstrated.